2018
DOI: 10.17556/erziefd.403476
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarında Psikolojik İyi Oluşun Yordayıcısı Olarak Algılanan Sosyal Yetkinlik ve Güvengenlik

Abstract: In this study, it was investigated to what extent the variables of perceived social competence and assertiveness of the pre-service teachers predicted their level of psychological well-being. This research was carried out depending upon relational screening model. The study group of the research included totally 580 students studying at Erzincan University, Faculty of Education in 2015-2016 academic year 205 males (35.3%) and 375 females (64.7%) determined with simple random sampling method. Age average of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…However, the results of some studies indicate that psychological well-being of pre-service teachers did not significantly differ depending on gender, age, program in which they are enrolled (Öztan Ulusoy & Konaklı, 2017), grade level and academic achievement (Kumcağız & Gündüz, 2016) variables. Yet, some studies found that personality traits and selfunderstanding (Sarıcaoğlu, 2011), various values (hedonism, universalism and self-transcendence) (Telef, Uzman, & Ergün, 2013), fear of happiness (Sarı & Çakır, 2016), self-consciousness (Demirci & Şar, 2017), selfdiscrimination (Karababa, Mert, & Çetiner, 2018) and perceived social competence and assertiveness (Ateş & Çelik, 2018) significantly predicted pre-service teachers' psychological well-being. Some studies detected significant relations between psychological well-being of pre-service teachers and some variables such as smart phone addiction (Kumcağız & Gündüz, 2016), physical and emotional abuse (Bozgün & Pekdoğan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of some studies indicate that psychological well-being of pre-service teachers did not significantly differ depending on gender, age, program in which they are enrolled (Öztan Ulusoy & Konaklı, 2017), grade level and academic achievement (Kumcağız & Gündüz, 2016) variables. Yet, some studies found that personality traits and selfunderstanding (Sarıcaoğlu, 2011), various values (hedonism, universalism and self-transcendence) (Telef, Uzman, & Ergün, 2013), fear of happiness (Sarı & Çakır, 2016), self-consciousness (Demirci & Şar, 2017), selfdiscrimination (Karababa, Mert, & Çetiner, 2018) and perceived social competence and assertiveness (Ateş & Çelik, 2018) significantly predicted pre-service teachers' psychological well-being. Some studies detected significant relations between psychological well-being of pre-service teachers and some variables such as smart phone addiction (Kumcağız & Gündüz, 2016), physical and emotional abuse (Bozgün & Pekdoğan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bireyin güçlüklerle baş edebilmesi için önemli bir beceridir. Kendini sosyal yetkinliğe sahip gören bireylerin psikolojik iyi oluşlarının da yüksekliğini yordamaktadır (Ateş ve Çelik, 2018). Diğer yandan etkin insiyatif alabilen sporcuların özgüveni ve sorunlarla baş etme becerilerinin, kendilerini olduğu gibi kabul etme ve çevresiyle iyi ilişki kurabildiklerini, bu bireylerin ise psikolojik iyi oluşlarının yüksek olduğu ortaya konmuştur (Özmen, 2019).…”
Section: Discussionunclassified